Hadronic re-acceleration at the Crab pulsar wind termination shock as a source of PeV gamma-rays - Spencer, Samuel; Mitchell, Alison; Reville, Brian (38th International Cosmic Ray Conference (ICRC2023), 2023)
Recent results from LHAASO and Tibet ASγ suggest that the Crab Nebula’s gamma-ray spectrum extends to the PeV energy range, however the production mechanisms of this highest energy emission remain unclear. It has been postulated that a secondary component of hadronic emission could explain the highest energy gamma-ray flux points, however the origin and acceleration mechanism for this hadronic population has yet to be explained. We postulate one scenario in which hadrons diffuse over time into the Crab pulsar wind nebula from the surrounding supernova ejecta, and are subsequently re-accelerated by the pulsar wind termination shock. We present results of direct particle transport simulations (including radial evolution) to determine if this scenario is viable over the lifetime of the Crab system.<br